Gallbladder tuberculosis: A rare case report with review of literature (Indian Journal of Case Reports, 2024)
Gallbladder tuberculosis (TB) is a rare disease, and it might be challenging to distinguish it from gallbladder cancer on clinical history and radiology. It frequently mimics carcinoma in patients who initially appear with a gallbladder mass. Gallbladder TB is only identified after histology of the resected specimen since radiography lacks pathognomic characteristics. Here, we describe a unique case of gallbladder TB that was incidentally identified when a 49-year-old lady was being evaluated for suspected gallbladder cancer. Histology of the gallbladder exhibits necrotizing granulomatous inflammation with the presence of numerous pink-colored, curved, and beaded acid-fast bacilli that were recognized on the Ziehl-Neelsen stain.